Microwave and conventional synthesis of new dihydrobenzimidazoquinazoline derivatives and their biological activities - Hasan, Hiba Ali (2018)
Inspired by the biological prominence of benzimidazoquinazoline, and trying to solve bacterial resistance problem as well as imbalance of antioxidant mechanisms inside our bodies, in this study, two series of eighteen dihydro-benzimidazoquinazoline derivatives (fifteen new derivatives except 39, 45, and 47) were synthesised. These two series were synthesised from the reaction of 2-(2-aminophenyl)-1Hbenzimidazole with two different series of aliphatic and aromatic aldehydes in a single step to investigate the activites of aliphatic as well as aromatic derivatives. The compounds were synthesized using two different techniques of traditional heating by reflux and microwave-assisted organic synthesis (MAOS). A comparative study was used to compare the efficiency of these two protocols to synthesise the same target compounds regarding the reaction time, percentage yield, purity of the compounds, and benignity towards the environment. Furthermore, the structures of eighteen compounds were confirmed by applying TLC, spectrometric analysis (1D and 2D NMR, FTIR, and GCMS), elemental analysis (CHN) and photoluminescence properties (PL). Accordingly, single crystal analysis was performed for five crystal samples for further confirmation. The in vitro antimicrobial and antifungal activity was assessed against a panel of bacteria and fungi: two Gram-positive (Staphylococcus aureus ATCC 43300 and Bacillus subtilis UPMC 1175), two Gram-negative (Pseudomonas aeruginosa ATCC 15542 and Salmonella choleraesuis ATCC 10708), and one fungus (Aspergillus brasiliensis ATCC 16404) to test their biological activity against new microorganisms. Furthermore, ABTS and DPPH antioxidant activities of these analogues were performed to investigate their scavenging activities. The microwave-enhanced synthesis method revealed superiority over its comparable method to synthesize the same type of compounds. The investigation of the antibacterial activity for both compound series (aliphatic and aromatic) revealed that some compounds gave moderate to good ability to inhibit Gram-positive bacterial growth, while only one compound in the aromatic family resulted in excellent inhibitory activity compared to tetracyclin standard drug. Neither of the two series displayed any inhibitory activity against the Gram-negative bacteria nor fungus. The ABTS scavenging activity for both series disclosed more powerful efficiency than for DPPH, as well as some of the derivatives displayed excellent antioxidant activity for both tests. Fifteen new compounds together with another three known derivatives were synthesized to test their biological activates. The study found that the dihydrobenzimidazoquinazolines were synthesised within minutes by only one step to produce ultra-pure fluorescent compounds with very good to excellent yields (82- 98%) in a more benign method towards the environment. The antimicrobial and antioxidant activities were investigated for these derivatives whereby, some of the compounds disclosed powerful activity that may help for future drug candidate development.